The Effect of Organizational Culture, Work Motivation, Job Satisfaction, and Career Development on The Performance of Employees at Institution “X” Building A - Dwi Kuntari, Arni; Pracoyo, Antyo; Haryanti, Enny; Joyosumarto, Subarjo (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research aims to analyse the performance of employees at Institution "X" Office A by considering factors such as organizational culture, work motivation, job satisfaction and career development. These factors were chosen as independent variables due their potential impact on employee performance, which is a dependent variable. The researcher used the Statistical Structural Equation Modelling (SEM) method especially the Partial Least Square (PLS) approach supported by SmartPLS, to process data obtained from a questionnaire survey conducted online using Google Form. The results of this research show that Organizational Culture and Work Motivation have a positive and significant effect on Employee Performance, whereas Job Satisfaction and Career Development have no effect on Employee Performance.